Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Phenethyl isothiocyanate mediates autophagy via the AMPK/mTOR signal pathway in human glioblastoma multiforme cells - Shu-Fen Peng; Hsin-Chung Liu; Fu-Shin Chueh; Hsu-Tung Lee; Sheng-Yao Hsu; Jaw-Chyun Chen; Jing-Gung Chung; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Selective depression of pyrite in molybdenite flotation using tiopronin as a non-alkalinity inhibitor: Performance and mechanism - Liwen Fu; Fen Jiao; Qian Wei; Jing Chen; Pan Gong; Chenyu Fan (Minerals Engineering, 2026)

ECCAS: An interactive web platform for assessing water-sustainable ecosystem productivity in large-scale dryland restoration - Ning Chen; Fen Gou; Weibin Zhang; Xinyao Xu; Nan Gao; Shuai Li; Bojie Fu; Yihe Lü; Shuai Wang; Jianwu Yan; Wei Liang (Journal of Environmental Management, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Application of a novel nanoparticle collector in the flotation separation of serpentine-containing pyrrhotite - Liwen Fu; Fen Jiao; Qian Wei; Zheyi Zhang; Pan Gong; Chenyu Fan; Tao Wei (Minerals Engineering, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Regional variations in vegetation greening and climate change impacts on gross primary productivity and evapotranspiration in the Loess Plateau - Fen Gou; Wei Liang; Bojie Fu; Ning Chen; Weibin Zhang; Zhao Jin; Jianwu Yan; Yihe Lv; Xingguo Mo; Nan Gao (Agricultural and Forest Meteorology, 2025)

In-situ stabilization of conjugated microporous polymer on sieve plates for multifunctional applications: Detection and removal of aflatoxins - Fei Ma; Yajie He; Fen Tang; Lina Fu; Liangxiao Zhang; Peiwu Li; Li Yu (Journal of Hazardous Materials, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

Maternal co-exposure to Cd and PS-NPLs induces offspring ovarian inflammatory aging via promoting M1 macrophage polarization - Ruiying Zhang; Penghui Nie; Yuankun Zhou; Juanjuan He; Lihong Wang; Hengyi Xu; Fen Fu (Chemico-Biological Interactions, 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Fractionation of phosphate oxygen isotope in the leachate of phosphogypsum during its infiltration - Fen Xu; Shun Fu; Haiyan Hu; Jiahao He; Shimeng Mou; Yanhua Xie (Journal of Environmental Management, 2025)

Large-scale ecological infrastructures enhance the productivity of agro-socio-ecological systems by reducing soil erosion in the Loess Plateau - Fen Gou; Wei Liang; Yan Liu; Bojie Fu; Zhenguo Wang; Weibin Zhang; Zhigang Chen; Jianwu Yan; Junyi Li; Yihe Lv (Journal of Environmental Management, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

6:2 chlorinated polyfluoroalkyl ether sulfonate (F–53B) induced nephrotoxicity associated with oxidative stress, inflammation and fibrosis in mice - Hua Wu; Yueying Feng; Ruiying Zhang; Hengyi Xu; Fen Fu (Chemico-Biological Interactions, 2025)

Two-way coupling fluid–structure interaction analysis on dynamic response of offshore wind turbine - Fen Li; Jiaojiao Fu; Jiahui Chen; Dan Hu (Marine Georesources & Geotechnology, 2024)

“Fast-charging” mechanism of Li3VO4 from the perspective of material science for lithium-ion battery - Rui Wang; Yuan Li; Gaoyang Li; Yihan Fu; Youzhi Wu; Fen Ran (Chemical Engineering Journal, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Converting fruit peels into biodegradable, recyclable and antimicrobial eco-friendly bioplastics for perishable fruit preservation - Shikai Zhang; Xinxin Cheng; Wenjing Yang; Quanbin Fu; Feng Su; Peng Wu; Yijing Li; Fen Wang; Houshen Li; Shiyun Ai (Bioresource Technology, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Assessing the impact of agriculture, coal mining, and ecological restoration on water sustainability in the Mu Us Sandyland - Nan Gao; Wei Liang; Fen Gou; Yan Liu; Bojie Fu; Yihe Lü (Science of The Total Environment, 2024)

A simple and effective approach to relieve stress and enhance cyclability of Si-based materials toward high-energy lithium-ion batteries - Shuting Fu; Xuxu Wang; Fen Yao; Qiao He; Fangxi Xie; Xin Wu; Shengfu Tong; Mingmei Wu (Chemical Engineering Journal, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

The spatial-temporal evolution and driving mechanism of Urban resilience in the Yellow River Basin cities - Haiyang Li; Ying Wang; Hongwei Zhang; Ruimin Yin; Chong Liu; Zhaojun Wang; Fen Fu; Jiaqi Zhao (Journal of Cleaner Production, 2024)

Study on the coupled and coordinated development of urban resilience and urbanization level in the Yellow River Basin - Haiyang Li; Chenxu Hu; Mengying Zhu; Jiarong Hong; Zhaojun Wang; Fen Fu; Jiaqi Zhao (Environment, Development and Sustainability, 2024)

Maternal F-53B exposure during pregnancy and lactation induced glucolipid metabolism disorders and adverse pregnancy outcomes by disturbing gut microbiota in mice - Yueying Feng; Hua Wu; Lihua Feng; Ruiying Zhang; Xiaoyan Feng; Wanzhen Wang; Hengyi Xu; Fen Fu (Science of The Total Environment, 2024)

Deriving fine-scale patterns of sea surface temperature in coral reef habitats using the Landsat 8 thermal infrared sensor - Xiu-Ling Zuo; Ke-Fu Yu; Bin-Ni Qin; Xiao-Peng Duan; Zuo-Fang Yao; Fen-Zhen Su (Frontiers in Marine Science, 2023)
The available sea surface temperature (SST) products are too coarse to assess the fine-scale (<1 km) SST variations related to coral bleaching. In this study, we proposed an optimal SST inversion model using Landsat 8 thermal infrared sensor (TIRS) images to derive fine-scale SST patterns in the coral reef habitats of the Xisha Islands, South China Sea. Our study included two parts: 1) six SST inversion models were developed using the radiative transfer method and the split window (SW) algorithm in the hot season and cool season, from which the optimal SST inversion model was determined; and 2) the optimal model was applied to 47 Landsat 8 TIRS images to derive the SST spatial and temporal pattern among the geomorphic zones of six reefs in hot and cool season conditions. Compared with the measured sea temperature data and the verified MODIS SST products, the SST6 model using the SW algorithm was optimal, with an RMSE of approximately 0.64°C in the hot season. The average SST results usually had a pattern of reef flat > lagoon > reef slope/offshore sea. The reef flat was usually approximately 0.05°C–0.2°C hotter than the lagoon in the hot season. The SST in the lagoon also increased from south to north and the shallow lagoon was usually warmer than the deep lagoon in the hot season. Our results suggested that scleractinian corals in the reef flat and the lagoon were more susceptible to bleaching-level thermal stress than other geomorphic zones. During the cool season, the SST fluctuated markedly among coral reefs and geomorphic zones.

Synthesis of size-controllable, yolk-shell metal sulfide spheres for hybrid supercapacitors - Yan Zhou; Yongsheng Fu; Tingting Zhang; Chenyao Hu; Fen Qiao; Junfeng Wang; Hyuk-Jun Noh; Jong-Beom Baek (Chemical Engineering Journal, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

The key iron assimilation genes ClFTR1 , ClNPS6 were crucial for virulence of Curvularia lunata via initiating its appressorium formation and virulence factors - Yuanyuan Lu; Jiaying Sun; Yibo Gao; Kexin Liu; Mingyue Yuan; Weida Gao; Fen Wang; Dandan Fu; Nan Chen; Shuqin Xiao; Chunsheng Xue (Environmental Microbiology, 2021)
Summary Iron is virtually an essential nutrient for all organisms, to understand how iron contributes to virulence of plant pathogenic fungi, we identified ClFTR1 and ClNPS6 in maize pathogen Curvularia lunata ( Cochliobolus lunatus ) in this study. Disruption of ClNPS6 significantly impaired siderophore biosynthesis. ClFTR1 and ClNPS6 did mediate oxidative stress but had no significant impact on vegetative growth, conidiation, cell wall integrity and sexual reproduction. Conidial germination delayed and appressoria formation reduced in Δ Clftr1 comparing with wild type (WT) CX‐3. Genes responsible for conidial germination, appressoria formation, non‐host selective toxin biosynthesis and cell wall degrading enzymes were also downregulated in the transcriptome of Δ Clftr1 and Δ Clnps6 compared with WT. The conidial development, toxin biosynthesis and polygalacturonase activity were impaired in the mutant strains with ClFTR1 and ClNPS6 deletion during their infection to maize. ClFTR1 and ClNPS6 were upregulated expression at 12–24 and 48–120 hpi in WT respectively. ClFTR1 positively regulated conidial germination, appressoria formation in the biotrophy‐specific phase. ClNPS6 positively regulates non‐host selective toxin biosynthesis and cell wall degrading enzyme activity in the necrotrophy‐specific phase. Our results indicated that ClFTR1 and ClNPS6 were key genes of pathogen known to conidia development and virulence factors.

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Role of cytoplasmic lncRNAs in regulating cancer signaling pathways - Pei-fen Fu; Xin Zheng; Xiao Fan; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Selenoprotein S inhibits inflammation-induced vascular smooth muscle cell calcification - Yali Ye; Weixia Bian; Fen Fu; Jian Hu; Hongmei Liu (JBIC Journal of Biological Inorganic Chemistry, 2018)

Functional Role of Matrix gla Protein in Glioma Cell Migration - Mu-Hui Fu; Chih-Yen Wang; Yun-Ti Hsieh; Kuan-Min Fang; Shun-Fen Tzeng (Molecular Neurobiology, 2018)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Suppressing Receptor-Interacting Protein 140: a New Sight for Salidroside to Treat Cerebral Ischemia - Tong Chen; Zhanqiang Ma; Lingpeng Zhu; Wenjiao Jiang; Tingting Wei; Rui Zhou; Fen Luo; Kai Zhang; Qiang Fu; Chunhua Ma; Tianhua Yan (Molecular Neurobiology, 2016)

Haze is a risk factor contributing to the rapid spread of respiratory syncytial virus in children - Qing Ye; Jun-fen Fu; Jian-hua Mao; Shi-qiang Shang (Environmental Science and Pollution Research, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

GSK-3β promotes PA-induced apoptosis through changing β-arrestin 2 nucleus location in H9c2 cardiomyocytes - Fen Chang; Jing Liu; Hui Fu; Jinlan Wang; Fang Li; Hongwei Yue; Wenjing Li; Jing Zhao; Deling Yin (Apoptosis, 2016)

Sodium orthovanadate suppresses palmitate-induced cardiomyocyte apoptosis by regulation of the JAK2/STAT3 signaling pathway - Jing Liu; Hui Fu; Fen Chang; Jinlan Wang; Shangli Zhang; Yi Caudle; Jing Zhao; Deling Yin (Apoptosis, 2016)

Comparison of NCEP ‐ NCAR and ERA ‐Interim over Australia - Guobin Fu; Stephen P. Charles; Bertrand Timbal; Branislava Jovanovic; Fen Ouyang (International Journal of Climatology, 2016)
This study compares observations of 22 climate variables [rainfall, minimum and maximum temperature, mean sea level pressure (MSLP), and air temperature, geopotential heights, relative and specific humidity, and u‐wind and v‐winds at 500 , 700 and 850 hPa] over Australia with NCEP‐NCAR (National Centers for Environmental Prediction‐National Center for Atmospheric Research) and ERA ‐Interim, two most often used reanalysis products. The results indicate that both NCEP‐NCAR and ERA ‐Interim generally reproduce the observed spatial patterns of long‐term mean annual rainfall, daily maximum/minimum temperature and MSLP, the monthly distribution (annual cycle) of rainfall and temperature, although temperature is generally better simulated than rainfall and ERA ‐Interim shows an overall better performance than NCEP‐NCAR in term of continental scale. In term of linear trends, both NCEP‐NCAR and ERA ‐Interim simulate observed trend signs in some regions, but not in others, and the spatial distributions of temperature trends are generally not as well simulated as that of annual rainfall for both NCEP‐NCAR and ERA ‐Interim. In addition, NCEP‐NCAR and ERA ‐Interim show similar spatial patterns of annual mean air temperature, geopotential heights, humidity and winds. This implies that studies using NCEP‐NCAR data could also make use of ERA ‐Interim to explore the range of uncertainties for the regions and climate variables where NCEP‐NCAR and ERA ‐Interim show differences. This conclusion may also apply to regions other than Australia. For example, the different trend signs of MSLP between NCEP‐NCAR and ERA ‐Interim could present a scientific challenging for climatic change studies using MSLP trends, and the split between large‐scale and convective rainfall would also have merits globally to understand if the differences between the two reanalysis data sets are global or if we see convergence on key areas, such as tropices and frontal systems.

Impacts of climate change under CMIP5 RCP scenarios on streamflow in the Huangnizhuang catchment - Fen Ouyang; Yonghua Zhu; Guobin Fu; Haishen Lü; Aijing Zhang; Zhongbo Yu; Xi Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Effects of light on the circadian rhythm of diabetic rats under restricted feeding - Tao Wu; Fen ZhuGe; Yali Zhu; Nan Wang; Qianru Jiang; Haoxuan Fu; Yongjun Li; Zhengwei Fu (Journal of Physiology and Biochemistry, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Vegetation cover variation in the Qilian Mountains and its response to climate change in 2000–2011 - Shao-fu Deng; Tai-bao Yang; Biao Zeng; Xi-fen Zhu; Hao-jie Xu (Journal of Mountain Science, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Reduced expression of aquaporin 9 in tubal ectopic pregnancy - Yin Fen Ji; Li You Chen; Kai Hong Xu; Ji Fen Yao; Yi Fu Shi; Xue Jun Shanguan (Journal of Molecular Histology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Molecular Cloning and Polymorphism of the Major Histocompatibility Complex (MHC) Class IIB Gene of Grass Carp (Ctenopharyngodon idella) - Zhong-Dian Dong; Yan Zhao; Qi Fan Zeng; Yong Fu; Fen Na Zhou; Xiang Shan Ji; Hui Wang (Biochemical Genetics, 2013)

Differential responses of peripheral circadian clocks to a short-term feeding stimulus - Tao Wu; Ou Fu; Ling Yao; Lu Sun; Fen ZhuGe; Zhengwei Fu (Molecular Biology Reports, 2012)

Analysis of gene expression profile of Arabidopsis genes under trichloroethylene stresses with the use of a full-length cDNA microarray - Bo Zhu; Ri-He Peng; Ai-Sheng Xiong; Xiao-Yan Fu; Wei Zhao; Yong-Sheng Tian; Xiao-Fen Jin; Yong Xue; Jing Xu; Hong-Juan Han; Chen Chen; Jian-Jie Gao; et al. (Molecular Biology Reports, 2012)

Stress responses to phenol in Arabidopsis and transcriptional changes revealed by microarray analysis - Jing Xu; Zhen-Hong Su; Chen Chen; Hong-Juan Han; Bo Zhu; Xiao-Yan Fu; Wei Zhao; Xiao-Fen Jin; Ai-Zhong Wu; Quan-Hong Yao (Planta, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

The impact of naturalized legumes on plant communities in Northern Taiwan: are we worrying too much? - Jenn-Kuo Tsai; Hao-Ting Sun; Chiao-Fen Chen; Chang-Fu Hsieh; Shan-Huah Wu (Plant Ecology, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Breeding bird species richness in Taiwan: distribution on gradients of elevation, primary productivity and urbanization - Pei‐Fen Lee; Tzung‐Su Ding; Fu‐Hsiung Hsu; Shu Geng (Journal of Biogeography, 2004)
Aim To examine the richness of breeding bird species in relation to elevation, primary productivity and urbanization. Location The island of Taiwan (120°–122° E, 22°–25° N). Methods We arranged bird species richness (BSR) data from 288 bird censuses undertaken in Taiwan into a 2 × 2 km quadrat system and calculated average values of elevation, primary productivity [surrogated by normalized difference vegetation index (NDVI)], and urbanization (surrogated by road density and percentage of built area) for each 2 × 2 km quadrat. Results Bird species richness showed a hump‐shaped relationship with elevation. It increased with elevation from sea level (10–64 species per 2 × 2 km quadrat), peaked around 2000 m (43–76 species), and then decreased with elevation towards its minimum at the highest elevation. Road density and percentage of built area decreased with elevation, and NDVI showed a hump‐shaped relationship with elevation and inverse relationships with road density and percentage of built area. BSR increased with NDVI and decreased with road density and percentage of built area. Linear and cubic terms of elevation together explained 31.3% of the variance in BSR, and road density explained additional 3.4%. The explanatory power of NDVI on BSR was insignificant after the effects of elevation and road density had been justified. Main conclusions We argue that urbanization plays an important role in the BSR of Taiwan. Urbanization might indirectly decrease BSR through decreasing primary productivity and therefore change the hypothetical inverse relationship between BSR and elevation into a hump‐shaped relationship. We also propose a time hypothesis that the biotic communities in the mid‐elevation zone of Taiwan had relatively longer periods of existence during the Pleistocene glacial cycles, which might be one underlying process of the observed hump‐shaped relationship between species diversity and elevation.

Genetic structure of endangered Rhodiola sachalinensis - Ting-Fen Yan; Yuan-Gang Zu; Xiu-Feng Yan; Fu-Jun Zhou (Conservation Genetics, 2003)